Analisis Aspek-Aspek Keberhasilan Pembelajaran di Indonesia: - Deasy Yunita Siregar; Lutfi Putri Khairani; Sonia Sabilla; Yusriani Yusriani; Rizki Putri Jasmine Siahaan (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The importance of this research lies in its contribution to the development of educational policy, the formulation of more effective teaching strategies, and the provision of direction to educational practitioners. By better understanding the factors that influence learning success, it is hoped that this research can become a valuable guide in improving the quality of education in Indonesia so that it meets global demands and prepares future generations optimally. Observational analysis research is a research approach in which researchers make direct observations of certain phenomena or events to gain a deeper understanding. In this context,